Whole of community facilitator support model: The rural preceptors' experience. Issue 4 (August 2018) - Zournazis, Helen Eleni; Marlow, Annette; Mather, Carey
Abstract: Background: In preparation for future needs of the health workforce there has been an increase of student enrolments into health-related courses resulting in competing demands for quality professional experience placements. Consequently, additional student and preceptor support is necessary to ensure positive learning outcomes for students placed in rural areas. Aim: To evaluate a whole of community facilitator model of support for nursing students and their preceptors in rural practice settings. Methods: An evaluation approach included a needs analysis; literature review and online surveys from preceptors, facilitators and nursing students. Findings: The results of the needs analysis and surveys identified how the whole of community facilitator model contributed to supporting preceptors to build placement capability and promote workforce development. The results revealed benefits to students and preceptors. Emerging themes from responses centred on the interrelationship between the learning, teaching and healthcare environments. Conclusion: Preceptors recognised the value of the whole of community facilitator model through their contribution of clinical and educational information, resources, modelling professional development, and provision of support. It was acknowledged multiple placement opportunities within a single community, enriched student experiences. With refinement, this model has potential to contribute to workforce development in other rural placement environments. To review the effectiveness of the model of facilitation, this paper focuses on the perspective of preceptors.